2002
DOI: 10.1086/344237
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of 2 Influenza A(H3N2) Clinical Isolates with Reduced Susceptibility to Neuraminidase Inhibitors Due to Mutations in the Hemagglutinin Gene

Abstract: Previous studies have shown that amino acid changes in the hemagglutinin (HA) gene of influenza viruses may result in decreased susceptibility to neuraminidase inhibitors (NAIs) in vitro. However, the emergence and characteristics of such HA variants in the clinical setting remain poorly studied. Herein, we report 2 influenza A(H3N2) isolates, from untreated patients, harboring an Arg229-->Ile substitution in the HA1 gene. The Ile229 variants were as sensitive as the Arg229 viruses to zanamivir and oseltamivir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
37
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 41 publications
(65 reference statements)
2
37
0
Order By: Relevance
“…Mouse models have allowed us to work with larger numbers of animals and have shown that individual genes from the 1918 influenza pandemic virus strain do in fact influence gene expression patterns and pathology in lungs infected with a mouse-adapted influenza virus (38a) and therefore are all the more likely to do so within the backbone of a human strain in a nonhuman primate model. Ferrets are also considered excellent models of human influenza (1,60,80), but there is a lack of ferret-specific genomic data, cDNA microarray slides, and immunological reagents which precludes their use in our studies. cDNA microarrays spotted with human genes are readily available, and nonhuman primate cDNA hybridizes satisfactorily to human cDNAs spotted on these arrays (59,63,74,78).…”
Section: Discussionmentioning
confidence: 99%
“…Mouse models have allowed us to work with larger numbers of animals and have shown that individual genes from the 1918 influenza pandemic virus strain do in fact influence gene expression patterns and pathology in lungs infected with a mouse-adapted influenza virus (38a) and therefore are all the more likely to do so within the backbone of a human strain in a nonhuman primate model. Ferrets are also considered excellent models of human influenza (1,60,80), but there is a lack of ferret-specific genomic data, cDNA microarray slides, and immunological reagents which precludes their use in our studies. cDNA microarrays spotted with human genes are readily available, and nonhuman primate cDNA hybridizes satisfactorily to human cDNAs spotted on these arrays (59,63,74,78).…”
Section: Discussionmentioning
confidence: 99%
“…We and others have observed changes in the receptor binding properties of the HA protein of H3N2 viruses during the 38 years that they have been circulating in humans (2,21,34). These changes, including a loss of the ability to agglutinate chicken red blood cells (RBC), suggest a recent reduction in the affinity of binding of the HA protein to its receptor, SA.…”
mentioning
confidence: 99%
“…The additional glycosylation can also decrease receptor binding activity, presumably due to occlusion of the receptor binding site pocket (1,27). Evolution of influenza A viruses in humans has brought about changes in receptor binding specificity and affinity; specifically, it has been observed that recent H1N1 and H3N2 clinical isolates no longer agglutinate chicken red blood cells (2,22,24,26,37). The fine receptor binding specificity of human influenza viruses is beginning to be understood, and indeed, a new preference of modern H3N2 isolates for binding Neu5Ac␣2,6Gal␤1-4GlcNAc (6ЈSLN) over Neu5Ac␣2,6Gal␤1-4Glc (6ЈSL) was recently described (23).…”
mentioning
confidence: 99%